2018
DOI: 10.3389/fnbeh.2018.00207
|View full text |Cite
|
Sign up to set email alerts
|

Neural Activity Predicts Reaction in Primates Long Before a Behavioral Response

Abstract: How neural activity is linked to behavior is a critical question in neural engineering and cognitive neurosciences. It is crucial to predict behavior as early as possible, to plan a machine response in real-time brain computer interactions. However, previous studies have studied the neural readout of behavior only within a short time before the action is performed. This leaves unclear, if the neural activity long before a decision could predict the upcoming behavior. By recording extracellular neural activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…This indicates that recording sites with a higher PCM showed a higher attentional modulation in the neurons recorded from them. Together with our previous observation that post-stimulus firing rate predicts reaction time 60 , our data suggest that phase coherence may influence the attentional processing of upcoming stimuli, leading to a more efficient behavior. Each time point in Fig.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This indicates that recording sites with a higher PCM showed a higher attentional modulation in the neurons recorded from them. Together with our previous observation that post-stimulus firing rate predicts reaction time 60 , our data suggest that phase coherence may influence the attentional processing of upcoming stimuli, leading to a more efficient behavior. Each time point in Fig.…”
Section: Resultssupporting
confidence: 84%
“…We hypothesize that attention shapes sensory processing by modulating inter-trial phase coherence within low frequency oscillatory activities. Given that attention enhances the behavioral detection of stimulus changes 61,62 , represented by LFPs as long as several seconds before and gamma coherence right before the response event occurs 60,63 , we asked if the modulation of phase coherence mediates the attentional influence on behavior. We conjecture that in those sets of trials with a higher phase coherence, the sensory cortex is prepared more effectively for processing sensory input, leading to a better performance in detecting stimulus changes.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that attention shapes sensory processing by modulating inter-trial phase coherence within low frequency oscillatory activities. Given that attention enhances the behavioral detection of stimulus changes (Gonzalez Andino et al, 2005; Prinzmetal et al, 2005), particularly represented by LFPs as long as several seconds before the response event occurs (Parto Dezfouli et al, 2018), we asked if it is the modulation of phase coherence that underlies this attentional influence on behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Esghaei et al showed that switching spatial attention to a neuron’s receptive field reduces the coupling of both gamma oscillations and spikes (both representative of local neural processing) to the low-frequency phase (Esghaei et al, 2015b; Parto Dezfouli et al, 2018) see also (Spyropoulos et al, 2018). These observations may challenge the current finding in that they suggested the coupling of local neural activity to the low frequency phase to have a suppressive role in attention.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary investigations into visual areas have shown that oscillatory components of local field potential (LFP) (Liu and Newsome, 2006;Womelsdorf et al, 2006;Smith et al, 2015;Khamechian et al, 2019) and neural spiking activity (Liu and Newsome, 2005;Smith et al, 2015;Parto Dezfouli et al, 2018) could provide useful information about how neural activities are linked to visuomotor behavior. These studies have reported a trial-by-trial correlation between the power of beta (10-30 Hz) (Smith et al, 2015), gamma, and high-gamma (50-200 Hz) (Liu and Newsome, 2006) LFPs and behavioral output.…”
Section: Introductionmentioning
confidence: 99%